2021
DOI: 10.1109/ojies.2021.3073142
|View full text |Cite
|
Sign up to set email alerts
|

Operation of Meshed Hybrid Microgrid During Adverse Grid Conditions With Storage Integrated Smart Transformer

Abstract: Microgrid faces various challenges such as reverse power flow, peak power demand, voltage limit violations, etc., due to significant installations of renewable energy sources (RESs) and electric vehicles (EVs). For continuous and effective operation of such a system, enhanced and complex control methodologies are needed. Smart transformer (ST) has emerged as a promising solution for overcoming such challenging issues. This paper proposes the operation of battery energy storage system (BESS) integrated ST in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Nonetheless, MHMs must integrate supervisory control coupled with an Energy Management System (EMS) to optimize network performance in terms of power quality, reduced line losses, and MG fault management capability [14]. Recently, EMS strategies have been proposed in MHM that integrate ESS and PVG in connection and disconnection maneuvers [29] [30]. Similarly, they have shown that voltage and load profile control can be realized by meshing the network in a ring configuration with bidirectional power flow control [14], facilitating independent active and reactive power management [31].…”
Section: B Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, MHMs must integrate supervisory control coupled with an Energy Management System (EMS) to optimize network performance in terms of power quality, reduced line losses, and MG fault management capability [14]. Recently, EMS strategies have been proposed in MHM that integrate ESS and PVG in connection and disconnection maneuvers [29] [30]. Similarly, they have shown that voltage and load profile control can be realized by meshing the network in a ring configuration with bidirectional power flow control [14], facilitating independent active and reactive power management [31].…”
Section: B Related Workmentioning
confidence: 99%
“…This index is adjusted by the power flow controller according to the required voltage level at both 𝑀𝑉 𝐷𝐢 and 𝐿𝑉 𝐷𝐢 from the conditions set by the power reference block and operating mode of the SST, which set the reference 𝑀𝑉 𝐷𝐢 π‘Ÿ and 𝐿𝑉 𝐷𝐢 π‘Ÿ . The functionality of the DAB coupled to the control layers allows integrating, typically, ESS on the 𝑀𝑉 𝐷𝐢 bus [33], even allowing to form of hybrid 𝐴𝐢 βˆ’ 𝐷𝐢 loops by integrating DER on the 𝐿𝑉 𝐷𝐢 bus port [25]. The third stage of the SST enables the connection of the MG to the SST and bidirectional power transfer between 𝐿𝑉 𝐷𝐢 and 𝐿𝑉 𝐴𝐢 .…”
Section: Figure 2 Some Of the Most Reasons For Preferring Sst Vs Lft ...mentioning
confidence: 99%
See 3 more Smart Citations